Development of A Multiplex PCR Method for Direct Detection of Common Mastitis Pathogens in Bovine Milk Samples - Kalin, Recep; Karahan, Murat; Acik, Mehmet Nuri; Tasdemir, Bulent; Cetinkaya, Burhan (Kafkas Univ, Veteriner Fakultesi Dergisi, 2017)
The aim of this study was to evaluate a simple and rapid DNA extraction method combined with a multiplex polymerase chain reaction (mPCR) for the identification of the major mastitis pathogens (Staphylococcus aureus, Streptococcus agalactiae, Escherichia coli and Mycoplasma bovis) from milk samples. Of the 200 California Mastitis Test (CMT) positive milk samples, 45 (22.5%), 21 (10.5%) and 11 (5.5%) were detected as positive for the presence of S. aureus, S. agalactiae and E. coli by culture, respectively. In mPCR by DNA isolation method optimised here, S. aureus, S. agalactiae and E. coli were detected in 26.5% (53/200), 12% (24/200) and 6% (12/200) of the milk samples, respectively. The abovementioned agents were observed in similar proportions when the samples were analysed by a commercial DNA isolation kit. On the other hand, M. bovis was not detected in any of the milk samples by either culture or mPCR methods. A significant difference was determined between the results of culture and mPCRs (P< 0.001). Diagnostic sensitivity and specificity of the optimised mPCR were calculated as 100% and 89.2% respectively, when culture results were considered as reference. The results suggest that the mPCR assay employed in this study could be used as an alternative routine diagnostic method for rapid, sensitive, and specific simultaneous detection of major mastitis agents in bovine milk samples.
Mastitisli inek sütlerinde önemli patojenlerin direkt tespiti için bir multipleks PCR yönteminin geliştirilmesi
Keywords: Mastitis; Major Pathogens; DNA isolation; Multiplex PCR